Modus Operandi of Illegal Mining Crime in The Area of Gold Mining - Komang Sulastra, Gusti (International Journal of Management and Education in Human Development, 2021)
This study aims to determine the shape of the modus operandi of the crime of illegal mining in the District of Rarowatu North Bombana Southeast Sulawesi province and to know the constraints faced by the police in dealing with criminal acts of illegal mining (illegal mining) in District Rarowatu North as well as the efforts made by the parties Police against the illegal mining crime. This research uses a normative juridical approach method that is supported by empirical materials that are based on primary data and information obtained directly from the community as a source of analysis material. The results of the study indicate that carrying out gold mining activities without an IPR (People's Mining Permit). The perpetrators carried out gold mining without a permit in the following way: The actors together built the machines at the mining location of North Rarowatu District, Bombana Regency. The internal constraints faced by the Bombana Resort Police in dealing with illegal gold mining activities are: Inadequate quantity and quality of investigator members in each unit, especially in the Bombana Resort Police Certain Crime Unit, and external obstacles, namely: the absence of witnesses who present, unclear witness statements, and expert witness statements that are not in accordance with the investigator's question. Efforts made by the Bombana Resort Police to overcome internal obstacles are: Conducting trainings, training, and evaluations that are specifically carried out to measure the ability (performance) of investigator members, and develop strategies to improve coordination between related agencies, while to overcome external obstacles namely: Submission of Summons II, explaining to the witness the obligations of the witness and showing the legal basis for the obligation of the expert witness.